Tradisi Pembacaan Q.S. At-Taubah [9]: 128-129 Di Pondok Pesantren Hidayatul Insan Palangka Raya - Putri Salsabila; Taufik Warman Mahfudz; Nor Faridatunnisa (al-Afkar, Journal For Islamic Studies, 2023)
The tradition of reciting Q.S. At-Taubah [9]: 128-129 at the Hidayatul Insan Islamic Boarding School in Palangka Raya is unique, where usually Q.S. At-Taubah [9]: 128-129 are read at the time of the Prophet's Birthday, but at the Hidayatul Insan Palangka Raya Islamic Boarding School, it becomes a routine practice by all the occupants of the hut after the obligatory prayers were performed. This research is qualitative research with a type of field research using Peter L. Berger's theory, namely the Sociology of Knowledge. The results showed that this practice was carried out by students of the Hidayatul Insan Palangka Raya Islamic Boarding School. They do this practice because they want fadilah or benefits such as peace of mind, and istiqomah in worship. The practice of remembrance is carried out after completing the Fajr and Maghrib prayers. As for how to practice the practice of remembrance reciting the readings 7 times after the wirid prayers at dawn and maghrib prayers. These practices can be done anywhere, whether in a prayer room, mosque, or room. Meanwhile, the effects felt by the perpetrators include consistency in worship, keeping the heart from mental illness, being given peace of mind and strength of rote memory so that it is given fluency in memorizing muraja'ah. As for the origin of this tradition, it is based on the hereditary habits of the previous Pondok Leaders and was given to the students to always practice.